Goat Meat: Production and Quality Attributes - Gawat M; Boland M; Singh J; Kaur L (MDPI (Basel, Switzerland), 2023)
Goat meat could be a sustainable source of red meat. Its farming requires minimal input, is suitable for free-range farming, and produces a healthier red meat option as it is lean. Although goat meat has advantages for meat production, it still needs to be established as a valuable part of the meat trade market. But, currently, goat meat production is less specialized; there is less intense breed selection for premium meat production, and often the animals are farmed with a multifunctional purpose, such as for their meat, fiber, and milk. The less structured goat meat industry contributes to the inconsistent quality of goat meat. This paper attempts to describe the characteristics of popular goat breeds and indigenous goats as a source of meat and the potential of various goat breeds for meat production. Additionally, this paper presents goat meat's quality and physicochemical and sensory attributes that are relevant to understanding the unique attributes of goat meat. Much work is needed for the goat meat processing industry to develop its potential.
Keywords: capretto; caprine meat; carcass characteristics; chevon; dairy goats; goat breeds; indigenous goat; meat composition; meat pH; tenderness